Language and Jamaican Literature (Altre Modernità, 2019)
Disrespected literatures are written in disrespected languages. Languagesare usually disrespected when the status of the people who speak them is low. In postplantationsocieties the respected language is the European language brought by thepeople who colonised the country. The disrespected language is usually a creole bornin the plantation environment where overseers speaking European languages andenslaved people speaking West African languages were forced to interact. In Jamaicathe respected official language is English and the disrespected popular language isJamaica Creole. The languages are lexically related and so give the impression of beingcloser than they are. In fact, Jamaican Creole is still regarded as “broken English” bypeople who have not paid attention to the linguistic analyses which indicate a strongstructural relationship to certain West African languages. These two languages, theofficial and the popular have accommodated each other in the Jamaican environmentwith speaker and situation determining use. A fascinating feature of thisaccommodation is the ability of the individual to switch from one language to the otherwithin the same speech event.This paper hopes to illustrate how I and other Jamaican writers have infused theformal/official language in which most of us write, with the popular language and sohave enriched the fabric that is the language in which Jamaican literature is written.Disrespected Literatures are written in Disrespected Languages. I am from Jamaicawhere the official language is Jamaican English, a respected language, and the popularlanguage is Jamaican Creole, commonly called Patwa, the disrespected language.Disrespected languages are hardly given the status of “language” except by linguists.They are called dialects or they are described as broken versions of respected languagesto which they are usually related lexically. So some people describe the Jamaicanpopular language as “broken English”. I have said elsewhere that if that is what it is, it isbroken into many very small pieces. The truth is that languages gain status from theirspeakers. An eminent linguist (Max Weinreich) quoting an unnamed friend, remarkedthat a language is a dialect with an army and a navy. Jamaican Creole, Patwa, even if itused the salaries of all its speakers could hardly sustain an army and a navy.